2002
DOI: 10.1046/j.1444-2906.2002.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Zn-binding protein in the digestive tract tissue of common carp

Abstract: The concentrations of Zn and sulfhydryl (SH) groups in the digestive tract tissue of common carp and some aquatic animals were studied. It was found that Zn and bound SH groups could be used as indicators for detecting the Zn‐binding protein in the digestive tract tissue of common carp. The digestive tract tissue of the fish underwent subcellular fractionation, and it was found that the nuclei/cell debris fraction contained most of the DNA (85%), Na+/K+‐ATPase (82%), organic phosphate (90%) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The digestive tract of common carp could be divided into five layers in histology (i.e. epithelial layer, lamina propria, submucosal layer, muscular layer, serosal layer) 13 . In fishes, a clear distinction between the connective tissue of the lamina propria and that of the submucosa layer is not possible 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The digestive tract of common carp could be divided into five layers in histology (i.e. epithelial layer, lamina propria, submucosal layer, muscular layer, serosal layer) 13 . In fishes, a clear distinction between the connective tissue of the lamina propria and that of the submucosa layer is not possible 14 .…”
Section: Discussionmentioning
confidence: 99%
“…reported that over 90% of the Zn in the nuclei/cell debris fraction of common carp digestive tract tissue could be easily extracted by 1 mM EDTA solution 4 . This EDTA‐extractable Zn was closely related to the bound SH groups of the tissue and it is suggested that the common carp tissue has a significant number of ‘active’ SH groups in its protein that bind to Zn 12 . The present study confirms that Zn is mainly bound to SH groups of the 43 kDa protein, since approximately 90% of the specific binding of Zn was abolished after treatment the protein with PCMB (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The zinc concentration was determined by atomic absorption spectrophotometry (Z‐8100, Hitachi, Tokyo, Japan) as described previously 12 . The zinc concentration in the connective tissue cells of the fish was determined as follows: the connective tissue cell suspension was centrifuged at 2000 × g for 10 min, the precipitated cells were then mixed with 2 mL of 6 mM EDTA dissolved in 50 mM Tris‐HCl buffer, pH 8.0 and centrifuged at 10 000 × g for 10 min.…”
Section: Methodsmentioning
confidence: 99%